A massive bead is attached to a wire in space with the following parametrization: In the above expression, is a point on the wire, is a spatial parameter, is a unit-vector in the direction of , and is a unit-vector in the direction of . Distances are in meters.
There is an ambient gravitational acceleration of in the direction. The bead moves without losses over the wire.
Starting at the origin, the bead has an initial speed of and is directed so that the -coordinate of the bead generally increases.
When the bead eventually stops moving and starts sliding back down again, how far is the bead from the origin (in meters)?
If the answer is , enter the result as .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Due to the fact that the gravitational field is a conservative field, the Δ E of energy does not depend on a particular walk of the point. So, we can write, for the 'Law of conservation of Energy', that
Δ E f , i = 0
Where E i is the energy of the point at the origin, while E f is the energy when it stops. Let's fix at z = 0 the potential energy E p = 0 . So at the beginning, the material point has just cinetic energy
E i = 2 1 m v i 2
At the end, when v f = 0 , it has just the amount of potential energy
E f = m g z f
So
m g z f − 2 1 m v i 2 = 0 , z f = 9 . 8 m
We have to find the parametrization of P . Vectors u 1 = ( 1 , 2 , 3 ) and u 2 = ( − 1 , 5 , − 3 ) give us directions, but we need versors. So let's multiply each vector by the opposite of its module.
∣ ∣ u 1 ∣ ∣ − 1 = 1 4 1 , ∣ ∣ u 2 ∣ ∣ − 1 = 3 5 1
u 1 = ( 1 4 1 , 1 4 2 , 1 4 3 ) , u 2 = ( − 1 4 1 , 1 4 5 , − 1 4 3 )
And so P becomes
P ( α ) = ( 1 4 α − 3 5 2 sin α , 1 4 2 α + 3 5 1 0 sin α , 1 4 3 α − 3 5 6 sin α )
Since we previously calculated z f , we know the z -coordinate of the ending point. So
9 . 8 = 1 4 3 α − 3 5 6 sin α , α = 1 0 . 9 5 8
Eventually
P f = P ( α = 1 0 . 9 5 8 ) = ( 3 . 2 6 6 , 4 . 1 6 8 , 9 . 8 )
The distance of P f from the origin is
∣ ∣ P f ∣ ∣ = 1 1 . 1 3 9 m